The use of vitamin B1 as a perineural adjuvant to middle interscalene block for postoperative analgesia after shoulder surgery - Alemanno, Fernando; Ghisi, Daniela; Westermann, Brigitte; Bettoni, Anela; Fanelli, Andrea; La Colla, Luca; Danelli, Giorgio; Cesana, Bruno Maria (Acta Biomedica Atenei Parmensis, 2016)
Background: Perineural administration of thiamine, via axonal flow, could strenghthen synthesis of ACh in the dorsal horn inhibitory interneurons, thus potentiating analgesia. The purpose of the present retrospective analysis is therefore to investigate whether adding perineurally 2 mg/Kg of thiamine to 0.75% levobupivacaine in patients undergoing middle interscalene block may prolong the duration of analgesia.Method: The hospital records of all ASA status 1-2 patients, undergoing a single-shot interscalene block for arthroscopic rotator cuff repair from January 2011 to May 2012 were retrospectively reviewed. All blocks were performed with 0.75% levobupivacaine or a solution of thiamine hydrochloride and 0.75% levobupivacaine. The local anesthetic solution, postoperative visual analogue score for pain at rest and rescue medication were registered. We calculated the time interval elapsing between block anesthetic mixture injection and the patient’s first analgesic requirement, ie time to end of analgesia. Eventual postoperative side effects were also reported.Results: 59 patients received 0.4 ml/Kg of 0.75% levobupivacaine (Group L) and 51 patients received a mixture of 2 mg/Kg of thiamine hydrocloride (maximum dose 200 mg) with 0.4 ml/Kg of 0.75% levobupivacaine (Group B1). Tea was 11.4 ± 3.0 hours in Group L versus 17.6 ± 3.0 hours in Group B1 (p < 0.001). The scores for pain in the two Groups at the time of the first analgesic rescue were comparable.Conclusion: The present retrospective analysis suggests that thiamine helps to prolong postoperative analgesia when added to the local anesthetic solution. Further prospective studies are necessary to confirm these preliminary results.Word count: 250